The Feasibility and Safety of the Clip-and-Snare Method with a Prelooping Technique for Gastric Submucosal Tumors Removal: A Single-Center Experience (with Video) - Qi Tang; Rui-Yue Shi; Jun Yao; Li-Sheng Wang; De-Feng Li (Canadian Journal of Gastroenterology and Hepatology)
Aim. This study compared the efficacy and safety of endoscopic submucosal dissection (ESD) combined with clip-and-snare method and a prelooping technique (CSM-PLT) with ESD alone for the treatment of gastric submucosal tumors (gSMTs). Methods. We retrospectively enrolled a matched group of 86 patients who received ESD combined with CSM-PLT or ESD alone from July 2010 to July 2020. The primary outcomes included complete resection, en bloc resection, and R0 resection. Results. Eighty-six patients with gSMTs were enrolled in ESD combined with CSM-PLT group and ESD group, respectively. There were no significant differences in gender, age, tumor size, tumor location, and tumor origin between the two groups. The complete resection, en bloc resection, and R0 resection rates were comparable between two groups (P=1, P=0.31, and P=0.25, respectively). There were no significant differences in terms of hospital stays, hospitalization cost, postoperative complications, and residual rate (P=0.42, P=0.74, P=0.65, and P=1, respectively) between the two groups. However, the ESD combined with CSM-PLT was associated with a shorter procedure duration and fewer intraoperative complications (P<0.001 and P=0.024, respectively). In addition, the incidence of intraoperative bleeding in ESD combined with CSM-PLT group was significantly lower than that in ESD group (P=0.04). Conclusion. Both ESD combined with CSM-PLT and ESD were effective and safe modalities for the treatment of gSMTs. However, ESD combined with CSM-PLT was associated with a shorter procedure duration and fewer intraoperative complications.